Developing a portfolio of policies and interventions to support pastoralists and rangelands - Ericksen, Polly J. (2021)
Presentation by Polly Ericksen, livestock and environment flagship leader, on the portfolio of rangelands work that has evolved in the flagship. This presentation was delivered as part of the golden eggs session of the final celebration and closing meeting of the CGIAR Research Program on Livestock in Oct 2021.